Kesejahteraan Psikologis Anak Usia Dini : Peran Interaksi Sosial di Lingkungan Hybrid (Online/Offline) - Nanda K. R. Awaliyah; Annisa Fahmi Mannassai; Nabila Nur’aini Pakaya; Noval Yakub; Nurain A. Arif (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This article discusses the importance of psychological well-being in early childhood within the context of social interaction in hybrid environments, which combine online and offline learning. The study aims to explore how social interaction influences children's psychological development and provides recommendations for best practices to support their well-being. The findings indicate that positive social interactions contribute to enhanced psychological well-being, while challenges in hybrid environments need to be addressed to support optimal child development.